Peran Penyidik dalam Menjamin Hak Tersangka : Kajian terhadap Implementasi KUHAP dalam Tahap Penyidikan - Syarif Hidayatulloh; Sigit Kamseno (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
In a criminal justice system that upholds the principle of justice, the protection of suspects' rights is a crucial and fundamental component. Investigators play a crucial role in ensuring suspects' rights are protected during the investigation process, including the right to legal counsel, the right to access information, and the right to be free from arbitrary prosecution. The aim of this study is to explore the role of investigators in guaranteeing these rights and highlight challenges in their implementation. The study revealed that many suspects did not receive legal assistance from the beginning of the examination, lacked understanding of their rights, and faced investigations that often violated due process of law. This problem is exacerbated by limited human resources, inadequate internal oversight, and lack of ongoing training for investigators. These factors contribute to the failure to enforce the rights of suspects as a whole, which impacts the fairness and integrity of the legal process. In an effort to realize a fast, simple, and inexpensive judicial process, as promised in Law Number 48 of 2009, this study emphasizes the need for reforms to strengthen the investigation process. The reforms include improvements in the aspects of supervision and more in-depth training of investigators on human rights, so that they can better understand and implement the protection of the rights of suspects. In addition, the use of technology in investigations, such as digital-based information systems to manage evidence and legal processes, can increase transparency and accuracy in every stage of investigation. Strengthening internal supervision mechanisms is also very important to minimize abuse of authority by investigators. On the other hand, it is important to periodically evaluate the application of standard operating procedures (SOPs) in investigations, in order to ensure compliance with applicable laws and provide justice for suspects.